2022
DOI: 10.3389/fpubh.2022.1087683
|View full text |Cite
|
Sign up to set email alerts
|

Effect of time-varying adherence to non-pharmaceutical interventions on the occurrence of multiple epidemic waves: A modeling study

Abstract: Non-pharmaceutical interventions (NPIs) play a central role in infectious disease outbreak response and control. Their usefulness cannot be overstated, especially during the early phases of a new epidemic when vaccines and effective treatments are not available yet. These interventions can be very effective in curtailing the spread of infectious diseases when adequately implemented and sufficiently adopted by the public. However, NPIs can be very disruptive, and the socioeconomic and cultural hardships that co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The largest decline was observed in December 2021 and January 2022 when the daily diagnosed cases exceeded 0.6 million people ( Figure 1A ), closely following the epidemic caused by the Delta variant. Long-term implementation of NPIs and successive waves caused pandemic fatigue and reduced people’s adherence to policies ( 44 , 45 ). More importantly, the results showed that the impact of NPIs was more correlated with the intensity of NPIs, with a decline in empirical effect along with the relaxation of NPIs ( Figure 2A ), which was consistent with previous estimation in Europe ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…The largest decline was observed in December 2021 and January 2022 when the daily diagnosed cases exceeded 0.6 million people ( Figure 1A ), closely following the epidemic caused by the Delta variant. Long-term implementation of NPIs and successive waves caused pandemic fatigue and reduced people’s adherence to policies ( 44 , 45 ). More importantly, the results showed that the impact of NPIs was more correlated with the intensity of NPIs, with a decline in empirical effect along with the relaxation of NPIs ( Figure 2A ), which was consistent with previous estimation in Europe ( 16 ).…”
Section: Discussionmentioning
confidence: 99%